RENEWAL OF THE AUTHORITY OF THE OMBUDSMAN INSTITUTION OF THE REPUBLIC OF INDONESIA IN SUPERVISING PUBLIC SERVICES IN INDONESIA - Lubis, Junaidi Usman; Nasution, Mirza; Afnila, Afnila (NOMOI Law Review, 2025)
Public services in Indonesia still face various challenges, both at the implementation level and regulatory aspects. One key issue is the weak effectiveness of oversight by the Indonesian Ombudsman regarding maladministration violations. Although Law Number 25 of 2009 concerning Public Services stipulates the Ombudsman's authority to carry out special adjudication as stipulated in Article 50, this provision has not been optimally implemented. As a result, the resolution of maladministration reports still relies on non-binding recommendations , thus creating legal uncertainty and legal disharmony within the public service system. This research uses a normative legal research method with a statutory and comparative legal approach. The study's findings indicate that regulatory weaknesses and the absence of a firm sanction mechanism for public agencies' non-compliance with the Ombudsman's recommendations have hampered the achievement of accountable and equitable public services. Therefore, regulatory reforms are needed to strengthen the Ombudsman's authority, including the implementation of special adjudication, administrative sanctions, social sanctions, and even criminal sanctions to provide legal binding force to recommendations, in order to ensure legal certainty and improve the quality of public service governance in Indonesia.